(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Hyperglycemia induces a higher rate of activation pathways responsible for inflammation which leads to microvascular and macrovascular complications, oxidative stress as well as apoptosis. In the pathological manifestation of hyperglycemic events, a raised level of inflammatory markers such as: IL6, TNF-? and C-reactive protein occurs which in turn promotes acute-phase of inflammation leading to signaling impairment of insulin function and insulin resistance. On the other hand, enhanced systemic inflammation due to periodontal diseases mediated by the release of IL-6 and TNF-? happens when associated with hyperglycemia. This review article deals with assessment on hyperglycemia and its correlation to dental pathologies with special reference to periodontitis and vice versa. Studies show that the paradigm shift in the oral microbiota due to hyperglycemic condition resulting in the increase in the pathogenicity of associated pathogenic microbes which results in increased inflammation and bone loss in periodontal pathologies. The extensive studies about the association between inflammatory periodontal disease and diabetes show the cyclic relationship between the two. Diabetes predisposes the individual to periodontal infections and also the later exacerbates or worsens the glycemic control in diabetic patients. Routine periodontal examination provides an insight for the early diagnosis of diabetes in undiagnosed patients and may reduce the worsening of metabolic control thereby preventing serious complications. Also the oral health of diabetic patients may be improved and well maintained with proper management of blood glucose levels. Although there are evidences in literature to establish correlation between Diabetes Mellitus associated with periodontitis and vice versa, still the outcomes are not conclusive. Therefore large-scale prospective epidemiological analysis are the only sought after approach to clearly bring in the connectivity between Diabetes and Periodontal disease